227k views
3 votes

\sqrt{x \sqrt{x \sqrt{x √(x....) } } } = \sqrt{4x + \sqrt{4x + \sqrt{4x + √(...) } } } \: pls \: help \: me

pls help me ......


User Ntjess
by
5.3k points

1 Answer

5 votes

First observe that if
a+b>0,


(a + b)^2 = a^2 + 2ab + b^2 \\\\ \implies a + b = √(a^2 + 2ab + b^2) = √(a^2 + ab + b(a + b)) \\\\ \implies a + b = \sqrt{a^2 + ab + b √(a^2 + ab + b(a+b))} \\\\ \implies a + b = \sqrt{a^2 + ab + b \sqrt{a^2 + ab + b √(a^2 + ab + b(a+b))}} \\\\ \implies a + b = \sqrt{a^2 + ab + b \sqrt{a^2 + ab + b \sqrt{a^2 + ab + b √(\cdots)}}}

Let
a=0 and
b=x. It follows that


a+b = x = \sqrt{x \sqrt{x \sqrt{x √(\cdots)}}}

Now let
b=1, so
a^2+a=4x. Solving for
a,


a^2 + a - 4x = 0 \implies a = \frac{-1 + √(1+16x)}2

which means


a+b = \frac{1 + √(1+16x)}2 = \sqrt{4x + \sqrt{4x + \sqrt{4x + √(\cdots)}}}

Now solve for
x.


x = \frac{1 + √(1 + 16x)}2 \\\\ 2x = 1 + √(1 + 16x) \\\\ 2x - 1 = √(1 + 16x) \\\\ (2x-1)^2 = \left(√(1 + 16x)\right)^2

(note that we assume
2x-1\ge0)


4x^2 - 4x + 1 = 1 + 16x \\\\ 4x^2 - 20x = 0 \\\\ 4x (x - 5) = 0 \\\\ 4x = 0 \text{ or } x - 5 = 0 \\\\ \implies x = 0 \text{ or } \boxed{x = 5}

(we omit
x=0 since
2\cdot0-1=-1\ge0 is not true)

User Sahdeep Singh
by
5.0k points